(3eGFI cJGH hcJGH (B:s (3cJH YQHjI CKQJ GdYGde(B.s ((3GdGeGQGJ GdYQHjI GdeJMOI (B:s (3OGFQI GdKbGaI hGdSjGMI, eQcR CHh XHj ddZI GdYQHjI,s, 2022)
(3jgOa eGFI cJGH hcJGH Edi GdJYQja HGdcJH GdeNJGQI, hHCge GdeUfajf aj GdCOH GdYQHj, hHGdCfhGY GdCOHjI GdeJfhYI GdJj YQagG GdJQGK GdYQHj (B((3GdNWGHI, GdebGeI, GdJQSd, GdbUjOI, GdQMdGJ GdSjQI GdPGJjI (B.....) (3ceG jQej GdeTQhY Edi EYGOI EMjGA GdfbGT Mhd GdcJH GdJQGKjI hCKQgG, hQaO GdeTGQjY GdegJeI HefGbTJgG hOQGSJgG hJQLeJgG hGdJaGYd eYgG hGdGSJdgGe efgG, hjegO GdWQjb CeGe OQGSGJ eJYOOI GdGNJUGUGJ hOQGSGJ ebGQfI YGHQI ddKbGaGJ hGddZGJ(B. s
(3gjFI GdJMQjQ (B: (3Ydi Hf Jeje, eMSf LGSe GdehShj, Ndjd GdTjN, SYjO MeOGf GdWfjLj, HdGd GdCQaI dj ; EYOGO djfG GdLeGd (B((3eMQQI(B)(3, O(B.(3TajbI hYjd, aGWeI TMhQj, QjcGQOh HGQjOj(B.s
Keywords: (3GdcJH GdYQHjIs -- (3eQGLYGJs; (3GdJQGK GdYQHjs -- (3eQGLYGJs